Johannes Franck (1854-1914): de eerste hoogleraar Nederlandse taal- en letterkunde in het Duitse taalgebied - Grave, Jaap (Studium, 2013)
Johannes Franck (1854–1914): the first Professor of Dutch Language and Literature in the German-speaking Countries. Johannes Franck (1854–1914) was the first Professor of Dutch language and literature in the German-speaking countries. Born Jewish but not a practising Jew, he found it impossible to get a chair in German language and literature because of the prevailing anti-Semitism in Prussia, Saxony and Bavaria at the time. In this article I will focus on his struggle to get a full professorship in Germany and the obvious but concealed anti-Semitism in Germany. I will then proceed to describe Franck’s study at Leiden University and his judgement on his colleagues in Germany and the Netherlands before dilating upon the ‘Berlin School’ he belonged to.